Theory and applications of dependable computer systems : proceedings of the Fifteenth International Conference on Dependability of Computer Systems DepCoS-RELCOMEX, June 29-July 3, 2020, Brunów, Poland /: proceedings of the Fifteenth International Conference on Dependability of Computer Systems DepCoS-RELCOMEX, June 29-July 3, 2020, Brunów, Poland. (2020) - Unknown
No abstract available